Influence of the Educational Factor on the Level of Intellectual Abilities of Police Officers - Smirnova, Olga; Horoshko, Valentina; Korchakova, Natalia; Pavelkiv, Vitalij; Rubskyi, Viacheslav; Kremenchutska Margarуta (Journal of History Culture and Art Research, 2020)
The article is devoted to the analysis of the diagnostics of the educational factor influence on the level of intelligence and general intellectual abilities in police officers. In the article, it was also aimed to describe theoretical and practical studies on the diagnosing of the intelligence level and general intellectual capacities in police officers, and to assess the influence of educational factors on the level of intelligence. The instruments used in the study during the professional-psychological selection included the Brief Qualifying Selection Test, the Intelligence Structure Test developed by Rudolf Amthauer et al., and Raven’s Progressive Matrices. Based on the empirical data analysis, it was proved that the police officers’ educational level had a significant impact on their integral index value, level and structure of intelligence, and general intellectual abilities.